STUDY ON APPLICATION OF PESTICIDE UTILIZATION IN FRUIT PEASANT LEVEL IN TURI SUBDISTRICT, SLEMAN DISTRICT OF SPECIAL TERRITORY OF YOGYAKARTA - Sipri Paramitha; Ichwani Kruniasih (Fakultas Pertanian, Universitas Janabadra, 2005)
level; base of peasant decision to use pesticide; and pattern of pesticide utilization.This research was conducted in Turi sub district, Sleman district. Interview was done over 35 fruit peasant and PPL of Turi sub district to complete information about control from government.Basic method used in this research is analytical descriptive method with non-parametric analysis statistic of Kolmogorov-Smirnov one sample test and parametric statistic to identify its distribution.Result of the research indicated that level of pesticide utilization on level of fruit peasant in Turi sub district is in appropriate level, with base of the decision to use pesticide as last action. Pattern of pesticide utilization are without pesticide and spraying pesticide when its attack reach economic threshold.